Extraction of Bioactive Compounds from Yellow Onion Peels: Taguchi-SAW Hybrid Optimization - Mehmet Güldane; Ali Cingöz (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to obtain an extract rich in bioactive components from yellow onion peels, which are generally considered waste material. Accordingly, a three-factor three-level Taguchi (L9) experimental design with three factors, namely ethanol concentration (A; 50%, 75%, 100%), extraction temperature (B; 30, 40, 50 °C), and sonication time (C; 10, 20, 30 min) was used to optimize the ultrasound-assisted extraction process of onion peel powders. Through Taguchi optimization, the optimum extraction conditions were determined as A2B3C2 to obtain the extract with the highest total phenolic matter (TPM) content and antioxidant activity (DPPH (%)). In addition, the extract produced under A2B1C2 conditions was found to be the richest in total monomeric anthocyanin (TMA) content with the highest level of color pigments. In order to determine the overall optimization conditions and to reduce the three-response optimization process to a single response, the simple sum weighting (SAW) method was used as a multi-criteria decision-making method. As a result of the optimization, it was concluded that an extract rich in bioactive components with optimal TPM and TMA contents and DPPH (%) value could be obtained as a result of sonication at 30 °C for 20 min to onion peel powders mixed with a solvent containing 75% ethanol (A2B1C2). The extraction conditions of bioactive components from yellow onion peels were successfully optimized by the Taguchi-SAW hybrid optimization method.